Memoirs as «biografo-latent» genre (Eurasian Journal of Philology Science and Education, 2016)
The article considers the memoirs and biographic sketch of N.S. Leskov devoted to the identity of the famous scientist-specialist in folklore and the writer-publicist P. I. Yakushkin – «Friendly memories of P.I. Yakushkin».The way of life of Yakushkin is presented by Leskov as a peculiar kind of Russian national «righteous person». Memories of Yakushkin represent a new type of chronicle composition caused by features of character of the personality about whom the memoirist tells.A peculiar genre of memoirs of Leskov can be defined as «biography – apocryphal» as its basis is the «initial» implication of facts of common knowledge of the biography of Yakushkin. In Leskov’s representation they are inseparable from «apocryphal» stratifications in the form of various hearings, certificates of contemporaries and eyewitnesses in whom also the originality of the era is endured by the author, and individual originality of character of the hero of literary memoirs is reflected.
Keywords: memoirs and biographic sketch; literary portrait; apocryphal story; folklore sketch; genre of memoirs.